Venture capital funding in Africa: a mixed-methods study of evolving ecosystems and financial discrimination - Christian Kabengele; Rüdiger Hahn (Journal of International Business Studies, 2025)
Africa's startup ecosystem is growing rapidly, yet venture capital (VC) funding remains disproportionately allocated to non-African founders. This study investigates the factors driving this disparity, focusing on institutional voids – gaps in legal frameworks, financial infrastructure, and market-supporting institutions – and investors' perceptions of risk and financial discrimination. We conducted 37 interviews with investors and entrepreneurs to identify the determinants of VC funding, including startup location, founder origin, and international networks. Additionally, a qualitative comparative analysis of 335 African fintech startups revealed the factor configurations that enable startups to secure high levels of VC investment. Historically, the findings reveal that non-African founders have benefited from investor homophily, a preference for investing in individuals with similar backgrounds, to mitigate the perceived risks related to institutional voids. By contrast, African founders faced greater barriers to funding. However, as Africa's VC ecosystem has matured, local founders have begun to overcome these obstacles. By linking institutional voids to homophily and embedding a postcolonial perspective, acknowledging how historical power dynamics and colonial legacies shape investor perceptions and market structures, this study sheds light on the systemic biases that shape VC funding. These findings offer actionable insights for investors, policymakers, and entrepreneurs aiming to foster a more inclusive VC landscape.
Keywords: 330; Venture capital; Africa; Institutional theory; Homophily; Emerging markets; Mixed-methods approach; Qualitative comparative analysis